2018
DOI: 10.20344/amp.9811
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Victims of Carbon Monoxide Poisoning in the Aftermath of a Wildfire: A Case Series

Abstract: RESUMOIntrodução: A intoxicação por monóxido de carbono pode ocorrer em diversos contextos. Results: The studied sample included 37 patients, mean age of 38 years, 78% males. Ten were firefighters, four children and two pregnant victims. Neurological symptoms were the most reported. Median carboxyhemoglobin level was 3.7% (IQR 2.7). All received high-flow oxygen from admission to delivery of hyperbaric oxygen. Persistence of symptoms was the main indication for hyperbaric oxygen. Median time to hyperbaric oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Major primary air pollutants, those emitted directly into the environment largely as a result of combustion of fossil and biomass fuels, include gaseous pollutants (such as sulfur dioxide [SO 2 ], nitrogen dioxide [NO 2 ], carbon monoxide [CO], and volatile organic compounds [VOCs]) and particulate matter (PM) (including carbonaceous aerosol particles, such as black soot). Although CO levels are often low outdoors in the developed world today (because of the use of emission controls such as catalytic converters on automobiles), high levels can be experienced near biomass burning sources, including wildfires 3 . In addition, secondary air pollutants are formed in the atmosphere from primary pollutants and include gaseous ozone (O 3 ), a major component of photochemical smog, formed in the atmosphere when nitrogen oxides (NO x ) and hydrocarbons such as VOCs react in the presence of sunlight.…”
Section: Sources and Levels Of Outdoor Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major primary air pollutants, those emitted directly into the environment largely as a result of combustion of fossil and biomass fuels, include gaseous pollutants (such as sulfur dioxide [SO 2 ], nitrogen dioxide [NO 2 ], carbon monoxide [CO], and volatile organic compounds [VOCs]) and particulate matter (PM) (including carbonaceous aerosol particles, such as black soot). Although CO levels are often low outdoors in the developed world today (because of the use of emission controls such as catalytic converters on automobiles), high levels can be experienced near biomass burning sources, including wildfires 3 . In addition, secondary air pollutants are formed in the atmosphere from primary pollutants and include gaseous ozone (O 3 ), a major component of photochemical smog, formed in the atmosphere when nitrogen oxides (NO x ) and hydrocarbons such as VOCs react in the presence of sunlight.…”
Section: Sources and Levels Of Outdoor Air Pollutionmentioning
confidence: 99%
“…Although CO levels are often low outdoors in the developed world today (because of the use of emission controls such as catalytic converters on automobiles), high levels can be experienced near biomass burning sources, including wildfires. 3 In addition, secondary air pollutants are formed in the atmosphere from primary pollutants and include gaseous ozone (O 3 ), a major component of photochemical smog, formed in the atmosphere when nitrogen oxides (NO x ) and hydrocarbons such as VOCs react in the presence of sunlight. Similarly, particulate sulfate (eg, sulfuric acid [H 2 SO 4 ]) and nitrate (eg, ammonium nitrate [NH 4 NO 3 ]) aerosols are commonly created in the atmosphere from SO 2 and NO x , respectively.…”
Section: Sources and Levels Of Outdoor Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis carried out in North America and Europe reported that PM2.5 and PM10 were both found to have a strong adverse association with lung adenocarcinoma. Particularly, the risk for lung cancer incidence or mortality rate increased 8% and 9% per each 10ug/m 3 increase in PM2.5 and PM10 concentration, respectively (198,203). In the participants who reported spending more than one hour per day outdoors, an adverse association of exposure to outdoor pollutions with adenocarcinoma was implicated (204).…”
Section: Pm Associated With Lung Cancermentioning
confidence: 97%
“…The costs are not only economic. The World Health Organization (WHO) affirms that fire trapping causes the main consequences of mortality from the incident during evacuations and air, nautical, and traffic accidents produced by reduced visibility to the firefighters, rescuers, and civilian population [10,11]. The risks are always implicit in a fire; for a forest firefighter, these would re-power when they do not have communication with the personnel to locate the fire origin point, not being able to define the spread direction for the creation of firebreaks, or not have well-identified safe areas and escape routes [12].…”
Section: Introductionmentioning
confidence: 99%